Neuroleadership in Virtual Workspaces: The Role of Trust, Psychological Safety, and Emotional Intelligence in Remote Teams - Singh, Radhika (Digital Repository of Theses, 2025)
This study examines the influence of neuroleadership practices on employee performance in virtual workplaces, mediated by trust, psychological safety and emotional intelligence. A quantitative approach was used to guide this exploratory research project to gain insights and understanding on the interlinkages between the variables and constructs. Descriptive statistics scoped the demographic and sampling population. Primary and secondary research methods informed the process to validate both the measurement model and the strength of the theoretical framework. An extensive literature review allowed scoping and focusing the research from taking it from a generic study to a more specific one that bridges academic research and practice on one of the most relevant leadership models in the last decade. It moved beyond generically looking at leadership to examine new competencies and models in the new world order, where AI and digital transformations are out of the confines of information technology departments and shaping corporate and business culture in new ways. Together, they have pushed human potential to new frontiers waiting to be discovered in the post pandemic world. In turn bringing focus to human performance and how best to allow it to thrive in new constraints. The findings established with reasonable clarity that neuroleadership influences employee performance both directly and indirectly, through its positive impact on emotional intelligence, trust and psychological safety. Each mediator represents distinct but interrelated psychological mechanisms that enable effective leadership in virtual work environments. The model has been tested and is valid for future researchers and corporations to invest in mediators and moderators of choice to determine what’s best for them. It is intended for this study to influence the way human talent is developed and shape leadership strategy in the future. It is limited in its purposive sampling and reliance on self-assessment that may allow unconscious biases. It will however be useful in studies that want to dive deeper into the neuropsychology and neurocognition aspects of human talent and potential, and leverage the brain’s ability to adapt and rewire behaviors through neuroplasticity. And seek to push the imagination of those working on new leadership models that will drive businesses in the next decade to maximize performance in a self-regulated manner that also influences others.